Sorting through Affirmative Action: Three Field Experiments in Colombia - Ibanez, Marcela; Riener, Gerhard (Journal of Labor Economics, 2018)
The use of affirmative action policies to promote female employment remains debated. Do affirmative action policies attract female applicants, and does that come at the expense of deterring highly qualified male applicants? In three field experiments in Colombia, we compare job seekers who are informed of affirmative action selection criteria before they apply with those who are told after applying. We find that the gains in attracting female applicants far outweigh the losses in male applicants. Moreover, our results indicate that affirmative action does not decrease the quality of the top 15th percentile of the pool of applicants.